(untitled) (PKP Barcelona 2019 Workshop, 2019)
• Go to https://workshops.publicknowledgeproject.org/index.php/barcelona2019 • Make a submission • Submit to any section you want • AFTER you complete your submission, you can log in to the site as a Journal Manager • Username: journalmanager • Password: pkpbcn2019